Tannin extracted from Penthorum chinense Pursh, a potential drug with antimicrobial and antibiofilm effects against methicillin-sensitive Staphylococcus aureus and methicillin-resistant Staphylococcus aureus - Qin, Junyuan; Yu, Lei; Peng, Fu; Ye, Xin; Li, Gangmin; Sun, Chen; Cheng, Fang; Peng, Cheng; Xie, Xiaofang (Frontiers in Microbiology, 2023)
Staphylococcus aureus is a conditional pathogenic bacteriuma. With the widespread use and abuse of antibiotics, various drug-resistant strains of S. aureus have emerged, with methicillin-resistant Staphylococcus aureus (MRSA) being the most common. Bacterial biofilm is an important factor in bacterial infection and drug resistance development. As a result, inhibiting biofilm formation has emerged as a therapeutic strategy. In this study, the chemical constituents and antimicrobial and antibiofilm effects of tannins isolated from Penthorum chinense Pursh (TPCP) were investigated. TPCP exhibits good antibacterial effects. The minimum inhibitory concentrations (MIC) and minimum bactericidal concentrations (MBC) to S. aureus and MRSA were 156.25 and 312.5µg/mL, and 312.5 and 625 µg/mL, respectively. According to the growth curves, TPCP significantly inhibited the growth of S. aureus and MRSA. The results of the crystal violet biofilm assay in conjunction with confocal laser scanning and scanning electron microscopy showed that TPCP destroyed preformed S. aureus and MRSA biofilms by eradicating or scattering biofilm cells. TPCP significantly inhibited the secretion of exopolysaccharides and extracellular DNA. Subsequently, the mechanism of biofilm eradication was preliminarily elucidated using qPCR. We examined the expression of icaA, cidA, sigB, agrA, and sarA genes in MRSA and found that TPCP inhibited biofilm formation by affecting the quorum-sensing system of bacteria. Our study shows that TPCP exerts antibacterial effects by disrupting the formation of bacterial biofilms, indicating that TPCP has clinical potential as a novel antibacterial agent for the prevention and treatment of S. aureus and MRSA infections.